Clinicopathologic Characterization of Bilateral Testicular Germ Cell Tumors With Immunohistochemical Evaluation of Mismatch Repair and BRAF (V600E) Genes Mutations. (September 2019) - Al-Obaidy, Khaleel I.; Trevino, Karen E.; Idrees, Muhammad T.
The incidence of bilateral testicular germ cell tumor (TGCT) is 1% to 5%. Despite the high rate of treatment success, resistance to chemotherapy has a detrimental effect. Some studies found MMR and BRAF gene mutations to be associated with chemotherapy resistance, which has not been found by others. However, the role of microsatellite instability (MSI) and BRAF mutations in bilateral disease has not been investigated. In this article, we studied the clinicopathologic characteristics and immunohistochemical expressions of MMR and BRAF in 13 patients with bilateral TGCT. Bilateral tumors were found in 4% of patients in our data. The mean ages at the first and subsequent diagnoses were 26.9 and 28.3 years, respectively. Eleven patients had metachronous disease; and the mean period between both tumors was 4.9 years. Six had mixed GCTs (MGCT) initially and later developed contralateral seminoma, 3 had bilateral MGCTs; 1 initially had pure embryonal carcinoma and subsequently MGCT and finally, 1 patient had initial seminoma and contralateral germ cell neoplasia in situ only. Of the patients with synchronous GCT, 1 had a MGCT and contralateral non-seminoma and 1 had seminoma and contralateral MGCT. In metachronous cases, 40% and 78% had an initial and subsequent stage of pT1, respectively. Hormonal and/or metastatic recurrence was observed in 30% of metachronous tumors. Six patients received chemotherapy, including patients with metastasis. No progression occurred after therapy. MLH1, PMS2, MSH2, and MSH6 staining was retained in all tumors. No BRAF staining was found. In conclusion, we found no association between bilateral TGCT and the MMR/MSI pathway and that subsequent metachronous tumors behaved much more indolently.